2017
DOI: 10.1515/aut-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation On Air and Thermal Transmission Through Knitted Fabric Structures Using the Taguchi Method

Abstract: Knitted fabrics have excellent comfort properties because of their typical porous structure. Different comfort properties of knitted fabrics such as air permeability, thermal absorptivity, and thermal conductivity depend on the properties of raw material and knitting parameters. In this paper, an investigation was done to observe the effect of yarn count, loop length, knitting speed, and yarn input tension in the presence of two uncontrollable noise factors on selected comfort properties of single jersey and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Tanveer Hussain et al [20] simplified the optimisation of multiple performance characteristics of cotton rotor yarn through the Taguchi method. Anindya Ghosh et al [21] used the Taguchi method to investigate the influence of yarn and knitting machine parameters on comfort properties of knitted fabric.…”
Section: Robust Design -Taguchi Methodsmentioning
confidence: 99%
“…Tanveer Hussain et al [20] simplified the optimisation of multiple performance characteristics of cotton rotor yarn through the Taguchi method. Anindya Ghosh et al [21] used the Taguchi method to investigate the influence of yarn and knitting machine parameters on comfort properties of knitted fabric.…”
Section: Robust Design -Taguchi Methodsmentioning
confidence: 99%
“…Generally, high R ct values of clothing are required to maintain the body under thermal equilibrium conditions. In hot environments or at high activity levels, evaporation of sweat becomes an important avenue for body heat loss, and fabrics must allow water vapor to escape in time to maintain the relative humidity between the skin and the first layer of clothing to about 50% [3][4][5][6]. Perspiration is the process of losing body heat due to the evaporation of moisture from the skin to the environment [7].…”
Section: Overview Of Thermal Resistance Testing On Thermal Manikinsmentioning
confidence: 99%
“…Ghosh et al investigated the effect of yarn count, loop length, knitting speed, and yarn input tension in the presence of two uncontrollable noise factors on selected comfort properties of single jersey and 1×1 rib knitted fabrics using the Taguchi experimental design. It is observed that yarn count and loop length have significant influence on the thermo-physiological comfort properties of knitted fabrics [31].…”
Section: Introductionmentioning
confidence: 99%